The Association Between Coronary Artery Disease and Hyperuricemia in Libyan Adults: A Cross-Sectional Study - Ali Fadhlullah; Ahmed Balha; Razk Abdalgwad (Khalij-Libya Journal of Dental and Medical Research, 2021)
Background and objectives. Hyperuricemia has been linked to coronary artery disease (CAD) development. We aimed in this study to examine the association between hyperuricemia and CAD among Libyan adults. Methods. This was a retrospective cross-sectional study of Libyan adults diagnosed with CAD and were divided into groups with high and normal serum uric acid. The data for patients were collected retrospectively from medical records. The likelihood occurrence of CAD in patients with hyperuricemia was determined by using the Bayesian one sample test. Results. In total, 97 patients with CAD were recruited in this study. 67 (69.1%) had CAD with high serum uric acid levels, while only 30 (30.1%) had CAD with normal serum uric acid levels. The mean age of patients at the start was 60 ± 11.89 for all patients. 53 (54.6%) of patients were females, and 44 (45.4%) (p = 0.863) were males, respectively. Hyperuricemia was significantly associated with the occurrence of CAD (p = 0.002). Conclusion. Amongst a cohort of Libyan adults, there was a significant relationship between hyperuricemia and CAD.